Computed-Tomography as First-line Diagnostic Procedure in Patients With Out-of-Hospital Cardiac Arrest - Adel, John; Akin, Muharrem; Garcheva, Vera; Vogel-Claussen, Jens; Bauersachs, Johann; Napp, L. Christian; Schäfer, Andreas (Frontiers in Cardiovascular Medicine, 2022)
Background Mortality after out-of-hospital cardiac arrest (OHCA) with return of spontaneous circulation (ROSC) remains high despite numerous efforts to improve outcome. For patients with suspected coronary cause of arrest, coronary angiography is crucial. However, there are other causes and potentially life-threatening injuries related to cardiopulmonary resuscitation (CPR), which can be detected by routine computed tomography (CT). Materials and Methods At Hannover Medical School, rapid coronary angiography and CT are performed in successfully resuscitated OHCA patients as a standard of care prior to admission to intensive care. We analyzed all patients who received CT following OHCA with ROSC over a three-year period. Results There were 225 consecutive patients with return of spontaneous circulation following out-of-hospital cardiac arrest. Mean age was 64 ± 13 years, 75% were male. Of them, 174 (77%) had witnessed arrest, 145 (64%) received bystander CPR, and 123 (55%) had a primary shockable rhythm. Mean time to ROSC was 24 ± 20 min. There were no significant differences in CT pathologies in patients with or without ST-segment elevations in the initial ECG. Critical CT findings qualifying as a potential cause for cardiac arrest were intracranial bleeding (N = 6), aortic dissection (N = 5), pulmonary embolism (N = 17), pericardial tamponade (N = 3), and tension pneumothorax (N = 11). Other pathologies were regarded as consequences of CPR and relevant for further treatment: aspiration (N = 62), rib fractures (N = 161), sternal fractures (N = 50), spinal fractures (N = 11), hepatic bleeding (N = 12), and intra-abdominal air (N = 3). Conclusion Early CT fallowing OHCA uncovers a high number of causes and consequences of OHCA and CPR. Those are relevant for post-arrest care and are frequently life-threatening, suggesting that CT can contribute to improving prognosis following OHCA.